The Epidemiology of Bovine Viral Diarrhea Virus in Low- and Middle-Income Countries: A Systematic Review and Meta-Analysis - Zirra-Shallangwa, Bibiana; González Gordon, Lina; Hernandez-Castro, Luis E.; Cook, Elizabeth A. J.; Bronsvoort, Barend M. de Clare; Kelly, Robert F. (Frontiers in Veterinary Science, 2022)
Bovine viral diarrhoea virus (BVDV) causes reproductive inefficiencies and negatively impacts the economy of low-and middle-income countries (LMICs). It is characterised by a combination of syndromes that result in poor production performance, calf morbidity and mortality. BVDV control is possible through the introduction of biosecurity measures, test-cull and vaccination programs as accomplished in high-income countries. Knowledge of BVDV epidemiology is limited in many LMICs which hinders implementation of effective control programs. We carried out a systematic review and meta-analysis to estimate the burden of BVDV, identify the risk factors related to its occurrence, as well as the health and economic impacts in production systems. Relevant BVD articles were collated from library databases. 690 abstracts and full texts were found in an initial search followed by filtering of 59 manuscripts. We accounted for quality and risk of bias in a meta-analysis. Prevalence, exposure and current infection at regional, production and farming system levels were estimated using logistic random effects meta regression models. Finally, we calculated the proportion of studies that addressed risk factors, health and economic impacts across different production systems to inform future preventative strategies in LMICs. Seroprevalence was high and varied between regions. Mean weighted prevalence was 39.5% (95%CI 25.0-56.1), 45.2% (95%CI35.9-54.8), 49.9% (95%CI25.5-74.3) and 21.6% (95%CI 0.5-56) for the sub-Saharan Africa, South America, Middle East, and Asia respectively. Seroprevalence varied across farming systems with smallholder farming showing the highest values. Herdsize was the most frequently reported risk factor with percentages of 20.6%, 33.3%, and 38.4% for dairy, beef and mixed systems respectively. Abortion (13.7% of papers) was the main reported health impact in dairy systems. Few papers reported Milk drop (4.6% of papers), no paper investigated the economic cost of BVDV within farming systems. Animal-level seroprevalence varied across all regions. Most of the studies focus on BVDV seroprevalence, there were few papers investigating risk factors, and health impacts, and even less investigating economic impacts. Future studies should focus on identifying risk factors and quantify the health and economic impacts across systems. Understanding these aspects is crucial to develop management strategies to apply across diverse production systems in LMICs.